2019
DOI: 10.1002/ecs2.2846
|View full text |Cite
|
Sign up to set email alerts
|

Food or furniture: Separating trophic and non‐trophic effects of Spanish moss to explain its high invertebrate diversity

Abstract: Foundation species are typically suggested to enhance community diversity non‐trophically by increasing habitat structure and mitigating physical stress, while their trophic role is considered of minor importance. Yet, there is little experimental evidence on the relative importance of trophic and non‐trophic effects and the interaction with patch size. Here, we transplanted different festoon sizes of living Tillandsia usneoides (Spanish moss) and structural mimics assessing the trophic and non‐trophic roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
6
1
4
Order By: Relevance
“…In our study, a large biomass of J. rubens , which forms finely branched structures on H. incurva , could have increased organic matter retention, thereby improving habitat quality for detritivores and omnivores. In contrast with studies from terrestrial systems (Angelini & Silliman, 2014; Borst et al., 2019), predators were not facilitated by epiphytes in our study. This could be explained by the fact that most of the predators are highly motile and could be, therefore, considered as transient components of the assemblage supported by H. incurva .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, a large biomass of J. rubens , which forms finely branched structures on H. incurva , could have increased organic matter retention, thereby improving habitat quality for detritivores and omnivores. In contrast with studies from terrestrial systems (Angelini & Silliman, 2014; Borst et al., 2019), predators were not facilitated by epiphytes in our study. This could be explained by the fact that most of the predators are highly motile and could be, therefore, considered as transient components of the assemblage supported by H. incurva .…”
Section: Discussioncontrasting
confidence: 99%
“…Dominance of detritivores, which feed on organic matter and transfer it to higher trophic levels, is often reported in epiphyte assemblages, suggesting that detritus‐based food webs mediate carbon transfer in systems with high epiphyte cover (Angelini & Silliman, 2014; Borst et al., 2019; Piazzi et al., 2018). For instance, Borst et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…functions) to animals, create stronger facilitation cascades than non-living secondary FS. Living secondary FS likely promoted biodiversity because they are edible and produce detritus, thereby supporting both consumer and decomposer-based communities, and by modifying local conditions through metabolic process including gas exchange and excretion 23 , 38 , 57 . Nevertheless, even mimics of secondary FS had positive effects on biodiversity, highlighting the universal importance of habitat space in affecting biodiversity 2 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies were either correlative or theoretical papers that assumed that the foundation species was unpalatable to or not consumed by most community members. An experimental study that used habitat mimics to separate the importance of trophic and non-trophic interactions found that both types of interactions were important for structuring communities (Borst et al, 2019). Consequently, the importance of foundation species' trophic interactions in structuring food webs is unclear.…”
Section: Introductionmentioning
confidence: 99%